Effectiveness of Subliminal Messages on Behavioral Changes in Watching Shows on Netflix (A Qualitative Study on University Students in Medan - Mahadi, Syah Hendra; Ananda, Sabilla Tri (CONTENT: Journal of Communication Studies, 2025)
This study aims to understand how subliminal messages in Netflix shows shape the viewing habits of students in Medan. In the digital age, subliminal messages are often used in media communication strategies to influence viewing habits that occur unconsciously. Netflix presents such messages through nonverbal elements such as body gestures, facial expressions, visual colors, sound design, as well as digital features such as autoplay and recommendation systems. This study uses a qualitative method with a constructivist paradigm to explore students' subjective experiences in interpreting the presence of subliminal messages in Netflix shows. Data were obtained through interviews with purposively selected informants and validated through source triangulation. The results show that students gradually form new viewing habits through repeated interactions with Netflix features and content. On the cognitive aspect, selective awareness of recommended shows emerged; on the affective aspect, emotional attachment to the visual and audio atmosphere was formed; while on the conative aspect, viewing habits occurred longer due to the continuous show system. This study provides an understanding of how subliminal messages work in digital media and the meanings constructed by students as a form of modern communication that is subtle and not fully realized.